Pengaruh Model Small Group Discussion terhadap Hasil Belajar Bahasa Indonesia pada Siswa Kelas V SDN Cempaka Baru 05 Pagi - Syakira Syamlan; Bayu Thomi Rizal (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research aims to evaluate the influence of the Small Group Discussion (SGD) model on the learning outcomes of Indonesian language subjects for class V students at SDN Cempaka Baru 05 Pagi. The research method used is a quantitative method with an experimental approach. This experimental approach involves an experimental design that aims to test the effect of the independent variable (treatment) on the dependent variable (outcome) in a controlled environment. The results of this research indicate that the application of the Small Group Discussion model has a significant influence on the learning outcomes of class V students at SDN Cempaka Baru 05 Pagi. Hypothesis testing through the T test and F test supports these findings in both the control and experimental classes. Based on researchers' observations, when the material is presented using Small Group Discussions, the learning process becomes more enjoyable, and students can further explore their potential and skills. The conclusion is that there is a significant influence from the application of the Small Group Discussion model on the Indonesian language learning outcomes of class V students at SDN Cempaka Baru 05 Pagi.